(untitled) (Research, Society and Development, 2022)
Despite the Craftsmanship incorporate great relevance, notable as a strong generator of employment and income, few academic studies deal with the skills of artisans as holders of businesses. Given this scenario, the present study aims to map and analyze the academic works on the subject of Marketing focused on Crafts. For that, the method of bibliometric research was applied, together with the analysis of the content of the articles that address this theme. Articles were searched in scientific databases recognized worldwide such as: Proquest, Web of Science, Capes, Scopus, Scielo and Spell. With this survey, we obtained 44 articles for analysis. The bibliometrics results showed that the topic has varied in relevance over the decades, with the years between 1994 and 2009 as the lowest production period, with only 6 publications, growing in relevance in recent years, being the biennium 2019/2020 the period of highest production with 15 of the 44 publications. With regard to authors and journals, the most prominent had 2 publications each. Regarding the analysis of the content of the articles, we have as a result that only 17 of the 44 articles actually address the topic of Marketing focused on artisanal production, with a slight advantage being observed by the quantitative research method (7 times) compared to the qualitative (6 times). This study found the need for union between artisan producers so that together they can have the necessary strength to face the adversities of the market.